2016
DOI: 10.1186/s13071-016-1383-y
|View full text |Cite
|
Sign up to set email alerts
|

Vector competence of Aedes vexans (Meigen), Culex poicilipes (Theobald) and Cx. quinquefasciatus Say from Senegal for West and East African lineages of Rift Valley fever virus

Abstract: BackgroundRift Valley fever virus (RVFV; Phlebovirus, Bunyaviridae) is a mosquito–borne, zoonotic pathogen. In Senegal, RVFV was first isolated in 1974 from Aedes dalzieli (Theobald) and thereafter from Ae. fowleri (de Charmoy), Ae. ochraceus Theobald, Ae. vexans (Meigen), Culex poicilipes (Theobald), Mansonia africana (Theobald) and Ma. uniformis (Theobald). However, the vector competence of these local species has never been demonstrated making hypothetical the transmission cycle proposed for West Africa bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 60 publications
0
40
0
2
Order By: Relevance
“…Studies have shown that RVFV epidemics typically follow periods of heavy rainfall conducive to large mosquito populations (Davies, Linthicum, & James, 1985;Hassan, Ahlm, Sang, & Evander, 2011;Leedale, Jones, Caminade, & Morse, 2016;Redding, Tiedt, Lo Iacono, Bett, & Jones, 2017) as well as the trade and importation of infected animals into susceptible regions (Napp et al, 2018). In Africa, RVFV is mainly transmitted by the Aedes aegypti mosquito, however, a growing number of studies have made it clear that other mosquito species present in Asia, Europe and North/South America are experimentally competent as RVFV vectors (Brustolin et al, 2017;Ndiaye et al, 2016;Turell et al, 2015). Therefore, if RVFV were to be introduced into other continents and their endemic mosquito populations, it could cause widespread epidemics and could seriously impact the health of human populations and economically important livestock herds.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that RVFV epidemics typically follow periods of heavy rainfall conducive to large mosquito populations (Davies, Linthicum, & James, 1985;Hassan, Ahlm, Sang, & Evander, 2011;Leedale, Jones, Caminade, & Morse, 2016;Redding, Tiedt, Lo Iacono, Bett, & Jones, 2017) as well as the trade and importation of infected animals into susceptible regions (Napp et al, 2018). In Africa, RVFV is mainly transmitted by the Aedes aegypti mosquito, however, a growing number of studies have made it clear that other mosquito species present in Asia, Europe and North/South America are experimentally competent as RVFV vectors (Brustolin et al, 2017;Ndiaye et al, 2016;Turell et al, 2015). Therefore, if RVFV were to be introduced into other continents and their endemic mosquito populations, it could cause widespread epidemics and could seriously impact the health of human populations and economically important livestock herds.…”
Section: Introductionmentioning
confidence: 99%
“…The Cx. quinquefasciatus population used in this study has been proven competent for Rift Valley Fever virus (RVFV) [22]. Both Culex species are vectors of many other arboviruses, including West Nile, Japanese encephalitis viruses [23,24] and RVFV.…”
Section: Discussionmentioning
confidence: 99%
“…v. arabiensis and C. poicilipes are confirmed vectors of RVFV in Senegal (Fontenille et al, 1998;Diallo et al, 2000;Ndiaye et al, 2016). C. tritaeniorhynchus is highly abundant and was identified as a RVFV vector in the 2000 outbreak in Saudi Arabia (Jupp et al, 2002).…”
Section: Model Structure and Assumptionsmentioning
confidence: 99%